Are Bioactive and Free Sex Steroids Associated with Bone Mineral Density and Bone Turnover Markers in Middle Aged Men? - Original Investigation - Melek Sezgin; Burak Çimen; Handan Çamdeviren Ankaralı; İsmet As; Neslihan Erçetin; Özlem Bölgen Çimen; Günşah Şahin (Galenos Yayinevi, 2009)
Aim: To investigate whether bioactive and free sex steroids are associated with bone mineral density (BMD) and bone turnover markers in middle aged men. Material and Methods: One hundred and fifteen out of 165 volunteers aged 35-65 years presenting to our outpatient clinic were included in the study. Serum albumin, total testosterone (T), total estradiol (E2), SHBG, osteocalcin (OC) and C-terminal telopeptide (CTx) levels were measured. Free and bioactive sex steroids, free androgen index (FAI) and free estrogen index (FEI) were calculated. BMD in the lumbar spine and the hip was measured in all participants and effects of sex steroids on BMD and bone turnover markers were investigated. Results: The mean age and the mean body mass index (BMI) in all participants were 52.4±7.8 years and 26.1±3.4 kg/m2 respectively. There was no significant difference in sex hormone levels and bone turnover markers between the individuals with osteoporosis and osteopenia and the individuals with normal BMD (p>0.05). There was a significant relation between age and FAI (r=-0.23, p=0.01), but there was no significant relation between age and bioactive and free sex steroids, FEI and SHBG. However, there was a positive correlation between BMI and bioactive E2 (r=0.35, p:0001), free E2 (r=0.29, p:0.002) and FEI (r=0.39, p=0.0001). After an adjustment for variables effective on BMD was made; no relation was found between BMD measures from the lumbar spine and the hip and serum bioactive sex steroids, free sex steroids, FAI, FEI and SHBG (p>0.05). However, there was a weak positive relation between serum bioactive T, FEI and OC, CTx levels (p=0.05). Conclusion: We think that bioactive and free sex steroids are not independent variables effective on BMD in the spine and the hip in middle aged men and that further studies are needed to elucidate the pathophysiology of idiopathic male osteoporosis. (From the World of Osteoporosis 2009;15:59-65)